Bacillus species: factories of plant protective volatile organic compounds - Poulaki, Eirini G; Tjamos, Sotiris E (Journal of applied microbiology, 2023)
Several studies have described the potential use of volatile organic compounds (VOCs) emitted by soil microorganisms, specifically of the genus Bacillus, as a sustainable solution for disease management in plants. The Bacillus species have been extensively studied as biocontrol agents (BCAs) due to their ability to inhibit pathogens, trigger induced systemic resistance (ISR) in plants, and enhance plant growth. The ability of the Bacillus species to produce long-lasting resting structures, such as endospores, makes them particularly appealing as BCAs. In recent years, there has been a growing body of research on the effects of Bacillus-emitted VOCs on plant pathogen growth and the triggering of ISR. This review aims to highlight recent advances in the understanding of the biological activities of Bacillus-emitted VOCs, identify new subjects for VOCs research, and stimulate interest in the academic and agri-business sectors for developing pre- and post-harvest application methods.